2020
DOI: 10.3390/e22020254
|View full text |Cite
|
Sign up to set email alerts
|

Entropy Generation Methodology for Defect Analysis of Electronic and Mechanical Components—A Review

Abstract: Understanding the defect characterization of electronic and mechanical components is a crucial step in diagnosing component lifetime. Technologies for determining reliability, such as thermal modeling, cohesion modeling, statistical distribution, and entropy generation analysis, have been developed widely. Defect analysis based on the irreversibility entropy generation methodology is favorable for electronic and mechanical components because the second law of thermodynamics plays a unique role in the analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 67 publications
1
5
0
Order By: Relevance
“…The average value for FFE is 23.79 MJ/m 3 K, with a standard deviation of 2.13. These results are in agreement with the reported value of FFE in a recent paper by Cai et al 56 They conducted independent fatigue experiments with carbon steel 1018 and reported that FFE = 23% ± 10% MJ/m 3 K deviation. The temperature and electric potential slope were calculated based on 10 s of the beginning of each test.…”
Section: Resultssupporting
confidence: 93%
“…The average value for FFE is 23.79 MJ/m 3 K, with a standard deviation of 2.13. These results are in agreement with the reported value of FFE in a recent paper by Cai et al 56 They conducted independent fatigue experiments with carbon steel 1018 and reported that FFE = 23% ± 10% MJ/m 3 K deviation. The temperature and electric potential slope were calculated based on 10 s of the beginning of each test.…”
Section: Resultssupporting
confidence: 93%
“…This new approach does take into account all these parameters and thus provides a better reflection of the real value of the irreversibility ratios (which are given in table 4), thus providing the true value of the entropy generation. 6.6563 10 -3 3.9287 10 -12 5.9022 10 -10 10 6 1.4340 10 -3 1.8235 10 -13 1.2716 10 -10…”
Section: The Irreversibility Ratios Calculation Methodsmentioning
confidence: 99%
“…Accurately determining the entropy generation in applied thermal engineering is the indispensable prerequisite for the design of different types of thermal exchanging devices [2]. Entropy generation has been and continues to be the subject of many research activities over the past decades, as shown by the significant review articles by Oztop and Al-Salem [3], Sciacovelli et al [4], and more recently by Kumar et al [5], and Cai et al [6]. Solving the entropy generation equation during fluid flows in a natural convection regime, which will be developed later, requires the calculation of a coefficient called "the irreversibility distribution ratio", oftentimes symbolized by the Greek letter φ.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A few recent studies can be found in many practical situations such as thermal designing of electronic assembly, optimal package designing of printed circuit boards, data center modeling, cooling of electronic device, thermal storage, examining defects in electronic components, etc. (Bairi, 2015; Fulpagare et al , 2018; Djebali et al , 2019; Xu et al , 2019; Cai et al , 2020). More accurate experimental models are available, and it can be noted that concentric square-shaped solids with various aspect ratios are considered enormously.…”
Section: Introductionmentioning
confidence: 99%